Resistance and Adaptation: The Transformation of Pesantren Salafiyah in West Sumatra Between Islamic Scholarly Traditions and the Demands of Modernity - Harmonedi Harmonedi; Yanti Novita; Rahma Hasanah; Suryadi Fajri; Aulia Rahmi Putri; Misra Misra (Santri: Journal of Pesantren and Fiqh Sosial, 2025)
This study aims to analyze the dynamics and dilemmas faced by Pesantren Salafiyah in West Sumatra in maintaining traditional Islamic education amidst the currents of modernization and globalization. The research approach used is a descriptive qualitative approach, with data collected through in-depth interviews, participatory observation, and document analysis. The research subjects included kiai, teachers or ustadz, santri, almuni, and the surrounding community from several pesantren salafiyah, namely Pesantren Ashhabul Yamin Lasi in Agam Regency, Pesantren al-Manaar Batuampar in Lima Puluh Kota, MTI III Kampung Candung, MTI Tengku Tuah in Lima Puluh Kota, Pondok, and MTI Batang Kabung. The study’s results indicate that pesantren salafiyah play an important role in preserving the treasures of classical Islamic knowledge by teaching “kitab kuning” (classical Islamic texts) using traditional methods such as bandongan, sorogan, and halaqah. However, pesantren faces complex challenges, including changes in educational policies, limited resources, leadership renewal, and public perceptions of the relevance of pesantren graduates in the modern world. Nevertheless, many pesantren demonstrate adaptive capabilities through selective integration of modern elements, such as the addition of a general curriculum, strengthened management, and the use of learning technology, without abandoning their scholarly identity. The principle of "al-muhafazhah 'ala al-qadim al-shalih wa al-akhdz bi al-jadid al-ashlah" (religious guidance, the guidance of the righteous) serves as the basis for maintaining a balance between tradition and innovation. With wise and collaborative management, pesantren salafiyah has the potential to become models of relevant and sustainable Islamic education.